China’s Greater Bay Area - Britta Kuhn (Wirtschaftsdienst)
Abstract Economic cooperation among mainland China, Hong Kong and Macao has deepened quickly since 2019. A roadmap for China’s southeastern province Guangdong promotes a common development of nine municipalities within the Pearl River Delta and the two Special Administrative Regions. The Chinese government wants this combined Greater Bay Area to become a highly innovative city cluster with world-class technologies and industries. Fully integrated transport networks and many pilot schemes are on their way. They will probably end the “one country, two systems“-principle much before schedule. However, the ambitious plan faces impediments such as political tensions, trade confl icts and the COVID-19 pandemic.